Micro and nanomechanics. Volume 5 : proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Starman, LaVern A.; Hay, Jennifer; Karanjgaokar, Nikhil (Springer, 2016)
Micro-and Nanomechanics, Volume 5 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fifth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: MEMS: Materials & Interfaces; Microscale & Microstructural Effects on Mechanical Behavior; Novel Nano-scale Probes; Nanoindentation & Beyond; Nanomechanics; Dynamic Micro/Nano Mechanics.
International conference proceedings.
Keywords: Microelectromechanical systems -- Congresses.; Nanotechnology -- Congresses.; elektronické knihy; electronic books